Successful treatment of equine corneal neovascularisation by subconjunctival aflibercept - Задорожний, Олег Сергійович; Насінник, Ілля Олегович; Король, Андрій Ростиславович; Пасєчнікова, Наталія Володимирівна (My University, 2023)
A 10-year-old Westphalian horse was presented for examination following a 4-week history of ocular trauma and mycotic ulcerative keratitis of the right eye, complicated with uveitis and corneal neovascularisation. The right eye was treated for corneal neovascularisation with a 0.1 mL (4 mg) subconjunctival injection of aflibercept. A single subconjunctival injection of aflibercept was sufficient for complete regression of corneal neovascularisation. This is the first reported case of corneal neovascularisation in a horse successfully treated with subconjunctival aflibercept.